Discovery of natural products exhibiting anti-quorum sensing activities against Pseudomonas aeruginosa PAO1 / Chong Yee Meng - Chong , Yee Meng (2018)
Quorum sensing (QS) generally refers to a phenomenon where the bacteria communicate and coordinates their phenotypes based on the population density by secretion and sensing of small and self-generated signaling molecules known as the autoinducers. Pseudomonas aeruginosa PAO1 is an opportunistic pathogen that employs the QS system to regulate its virulence factors, among others. This thesis aimed to study the effects of the plant extracts against the P. aeruginosa PAO1 QS-regulated virulence factors which includes LecA, pyocyanin, swarming, elastase, staphylolytic activity and biofilm. Out of the 15 plants extracts that were screened for anti-QS activities, Garcinia mangostana was chosen for purification using column chromatography with silica gel and catechin was isolated as the bioactive molecule which acts as QS inhibitor. Besides that, a total of 50 purified single compounds of plant origins obtained from Department of Pharmacology, Faculty of Medicine, University of Malaya (collaboration work) were also assessed for their potential antagonistic action on P. aeruginosa PAO1 QS system. By using the bioassay guided isolation, malabaricone C which was purified from Mystrica cinnamomea with preparative HPLC was found to inhibit the selected virulence determinants of P. aeruginosa PAO1 such as pyocyanin, swarming as well as biofilm formation. Both catechin and malabaricone C was shown to target the signal receptor of the P. aeruginosa PAO1 QS system. The transcriptomic analysis with RNA-sequencing technology was carried out in order to study the gene expression of P. Aeruginosa PAO1 treated with catechin and malabaricone C. The sequence analysis revealed that catechin down-regulated some QS-regulated genes including pchC, pchG, pchR, pchD, pchF, pchE, pchA, fptA, ampO, ampP, yieF, pscO, eraR, lipH, nasS and napB while malabaricone C down-regulated genes like lhpM, yieF and nasS. The data obtained in this study validate the idea that explore the higher plants as rich source of anti-QS compounds that can attenuate the bacteria virulence and may be valuable source for novel drug discovery especially with the emergence of multidrug resistant (MDR) bacteria that render the antibiotic treatments less efficient.